2014
DOI: 10.1007/s00259-014-2783-x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline metabolic tumour volume is an independent prognostic factor in Hodgkin lymphoma

Abstract: TMTV0 is more relevant than tumour bulk for predicting the outcome in patients with HL, and adds a significant prognostic insight to interim PET response assessment. The combination of TMTV0 and ΔSUVmaxPET0-2 made it possible to identify three subsets of HL patients with different outcomes. This may guide clinicians in their choice of therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 35 publications
5
118
2
7
Order By: Relevance
“…This method used the 41% SUV max threshold method, as recommended by European Association of Nuclear Medicine (EANM), and because of its high interobserver reproducibility already described in lymphoma (23). A volume of interest was set around each lesion (node or organ involvement) as described previously (10,13,23). Bone marrow involvement was included in volume measurement only if there was focal uptake.…”
Section: Pet/ct Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This method used the 41% SUV max threshold method, as recommended by European Association of Nuclear Medicine (EANM), and because of its high interobserver reproducibility already described in lymphoma (23). A volume of interest was set around each lesion (node or organ involvement) as described previously (10,13,23). Bone marrow involvement was included in volume measurement only if there was focal uptake.…”
Section: Pet/ct Parametersmentioning
confidence: 99%
“…New promising PET metrics derived from baseline PET, allowing an estimate of tumor burden and metabolism, are proposed as biomarkers: the total metabolic tumor volume (TMTV) which is the sum of the regions of the local tumors with FDG uptake; the total lesion glycolysis (TLG) which is the sum of these regions weighted by the intensity of their FDG uptake. Retrospective studies have at least shown that a high TMTV was significantly associated with a worse PFS and/or overall survival (OS) in DLBCL (10,11) but also in other type of lymphoma, in primary mediastinal large B-cell lymphoma (12), in Hodgkin lymphoma (13), and in peripheral T-cell lymphoma (14).…”
Section: Introductionmentioning
confidence: 99%
“…It can be relative, using a percentage of the maximum uptake. A threshold of 41% of the SUV max within the lesion, recommended by the European Association of Nuclear Medicine for solid tumors (7), has been used in patients with Hodgkin lymphoma (4), diffuse large B cell lymphoma (3), and PTCL (5), with a good interobserver reproducibility. However, because lymphomas are heterogeneous disease with several tumor sites with a wide range of volumes, SUVs, and tumor background ratios, the adaptive segmentation methods might be of interest for TMTV measurement and could be proposed as an alternative to fixed thresholding methods.…”
mentioning
confidence: 99%
“…46 In addition, a recent analysis examined the prognostic importance of baseline (pretreatment) total MTV in untreated HL patients. 47 Baseline total MTV more accurately predicted outcome than tumor bulk and was prognostic in multivariate analysis for PFS.…”
Section: New Techniquesmentioning
confidence: 92%